2022
DOI: 10.1371/journal.pone.0270378
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compliance to Hand hygiene during COVID-19 on intestinal parasitic infection and intensity of soil transmitted helminthes, among patients attending general hospital, southern Ethiopia: Observational study

Abstract: BackgroundIntestinal parasitic infection (IPIs) is one of the major health problems in Sub -Saharan Africa where water, sanitation and hygiene practices are inadequate. Taking into account the national level implementation of intensive hand hygiene against COVID-19 pandemic and general protective effect this study assessed its effect on intestinal parasite.ObjectiveThis study aim to investigate the effect of compliance to hand hygiene practice on the prevalence of intestinal parasitic infection (IPIs) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
0
3
0
2
Order By: Relevance
“…In addition, this study revealed a lower prevalence of helminthic infection compared with LMICs (Assemie et al, 2021; Degarege et al, 2022), although there were severely poor hygiene practices, awareness, and knowledge. Since this study was conducted during the COVID‐19 pandemic, good hand hygiene compliance might have affected the findings (Seid et al, 2022). Despite helminthic infection rates in several developed and upper middle‐income countries (Wong et al, 2021), the number of helminthic‐infected children in Bangladesh is still high, as helminthic infections can be asymptomatic (Kpene et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study revealed a lower prevalence of helminthic infection compared with LMICs (Assemie et al, 2021; Degarege et al, 2022), although there were severely poor hygiene practices, awareness, and knowledge. Since this study was conducted during the COVID‐19 pandemic, good hand hygiene compliance might have affected the findings (Seid et al, 2022). Despite helminthic infection rates in several developed and upper middle‐income countries (Wong et al, 2021), the number of helminthic‐infected children in Bangladesh is still high, as helminthic infections can be asymptomatic (Kpene et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide scabies affect about 300 million persons annually in all races, social classes, and age groups and the highest incidence is supposed to occur in tropical low-resource environments (Sarwar, 2023). It is related to considerable disease among certain patient groups and is prevalent in several subtropical and tropical communities (Seid et al, 2022). Sexual promiscuity, undernourishment, overcrowding, poor hygiene, poverty, and institutionalization have been suggested as substantial risk factors and often epidemics occur in wars when these risk factors increase (Trüeb et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Mevcut tahminler, dünya nüfusunun en az dörtte birinin bağırsak parazitleriyle enfekte olduğunu ve 450 milyon kişinin bu hastalıkları geliştirdiğini gösteriyor. İnsanlarda yaygın olarak görülen bağırsak parazit enfeksiyonlarının çoğunun fekal oral yolla doğrudan elden ağza veya dolaylı olarak yiyecek ve su yoluyla bulaştığı göz önüne alındığında, WASH (su, sanitasyon ve hijyen), kişinden kişiye geçişin önlenmesinde etkili bir müdahale yöntemi olarak kabul edilmektedir (3)(4).…”
Section: Introductionunclassified